2022
DOI: 10.1111/jth.15607
|View full text |Cite
|
Sign up to set email alerts
|

An update on the global use of risk assessment models and thromboprophylaxis in hospitalized patients with medical illnesses from the World Thrombosis Day steering committee: Systematic review and meta‐analysis

Abstract: Introduction: Venous thromboembolism (VTE) is a leading cause of cardiovascular morbidity and mortality. The majority of VTE events are hospital-associated. In 2008, the Epidemiologic International Day for the Evaluation of Patients at Risk for Venous Thromboembolism in the Acute Hospital Care Setting (ENDORSE) multinational

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
33
0
5

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 31 publications
(41 citation statements)
references
References 50 publications
3
33
0
5
Order By: Relevance
“…Adequacy of thromboprophylaxis has been poorly addressed across studies. 2 Furthermore, there has been a wide inconsistency of the definition in studies and guidelines. 3 , 4 , 5 , 6 The ACCP guideline has proposed three main attributes for appropriate thromboprophylaxis 4 : (i) Patients at increased VTE risk should receive pharmacological thromboprophylaxis at an appropriate dosage; (ii) patients at low risk for VTE should not receive pharmacological thromboprophylaxis; (iii) patients at high risk of VTE and high risk of bleeding should receive mechanical thromboprophylaxis.…”
Section: Adequacy Of Thromboprophylaxismentioning
confidence: 99%
See 3 more Smart Citations
“…Adequacy of thromboprophylaxis has been poorly addressed across studies. 2 Furthermore, there has been a wide inconsistency of the definition in studies and guidelines. 3 , 4 , 5 , 6 The ACCP guideline has proposed three main attributes for appropriate thromboprophylaxis 4 : (i) Patients at increased VTE risk should receive pharmacological thromboprophylaxis at an appropriate dosage; (ii) patients at low risk for VTE should not receive pharmacological thromboprophylaxis; (iii) patients at high risk of VTE and high risk of bleeding should receive mechanical thromboprophylaxis.…”
Section: Adequacy Of Thromboprophylaxismentioning
confidence: 99%
“… 1 , 2 Although most VTE events occurring during hospitalization are not associated with symptoms and their clinical impact is probably not substantial, about 65% of the events may be preventable by appropriate thromboprophylaxis. 1 , 2 Despite this, institution of thromboprophylaxis is still unsatisfactory among hospitalized patients with marked geographic differences. 1 , 2 …”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“… 21 A systematic review and meta-analysis showed that from 50.5% of patients with an indication to thromboprophylaxis, 54.5% had received adequate thromboprophylaxis, and bleeding, thrombocytopenia, and renal/hepatic failure were commonly specified contraindications to thromboprophylaxis. 22 Hence, we aimed to assess VTE risk, thromboprophylaxis practice, and outcomes using the Padua prediction score (PPS) in hospitalized medical patients at Tibebe Ghion Specialized Hospital (TGSH).…”
Section: Introductionmentioning
confidence: 99%